Formulation and Evaluation of Flurbiprofen Oral Film - Shaimaa N. Abd-Alhammid; Haider H.Saleeh (College of Pharmacy University of Baghdad, 2017)
Fast dissolving film can be defined as a dosage form, which when placed in the oral cavity. It will rapidly disintegrate and dissolves to release the medication for oral mucosal absorption or allow for the gastrointestinal absorption to be achieved when swallowed. Flurbiprofen is non-steroidal anti-inflammatory agent with antipyretic and analgesic properties and can be used   in low doses 8.75 mg as analgesic and anti inflammatory agent in sore throat infection. This study aims to   formulate flurbiprofen as oral dissolving films,   to improve the effective relief of pain with severe sore throats with little or no adverse effect. Nine formulas were prepared using solvent-casting method, and the effect of different formulation variables on the physical and mechanical properties of the prepared films, besides to the drug release behavior was evaluated.  It was found that, the prepared oral film of flurbiprofen that contains hydroxypropyl methylcellulose alone showed the fastest in- vivo disintegration time (30 sec.) Among other investigated polymers. The drug release rates was also observed The prepared formula F1 which contains HPMC in concentration of (54% w/w), PEG 400 (16% w/w) showed the fastest disintegration time 30seconds, Drug release was 77.5% within 2minutes with satisfactory mechanical properties. The overall results suggested that the prepared formula of flurbiprofen can be conveniently administered orally in the form of an oral film for sore throat infection.   Keyword:Oral strip, fluriprofen, HPMC polymer.